CONCEPTUALIZAREA ÎNVĂŢĂRII SITUATIVE DIN PERSPECTIVA COMUNICĂRII DIDACTICE - USM ADMIN (Moldova State University, 2010)
The pedagogy takes into consideration two types of totality: (1) its own conceptual matrix, which is par excellence abstract, and (2) the totality of educational facts. The conceptual Gestalt, through which the theory assimilates the significance of educative facts, is based on the understanding context. Firstly, the meanings of the theory taken as a whole, i.e. the meanings of inter-conceptual connections, correspond to the real world. Secondly, the educational situations are pre-significant, in other words significance receivers and are absorbed in the pedagogic approach. The new architecture of the educational phenomenon multiplies and stratifies the interpretation levels. The new limits of the pedagogy reside in the educational phenomenon concept, which includes the ontic relevance and the noetic one. This phenomenon is an essential component of the social environment. If against all reasons it is removed, the social would be emptied of its content. Therefore, we could talk about the implicit educational ontic for the human existence. Paradoxically, as soon as we enter the real world, we can see the educational phenomenon losing the conceptual simplification and enhancing its factual complexity. The phenomenon displays itself irregularly at this level, as educational experience and event. More clearly, it is controlled and directed within specific environments, e.g. school environment, where it consists in a number of instructive situations. In addressing the learning situation, the knowledge and skills are acquired in contexts that mirror the way the knowledge is assimilated and put into practice in daily situations. This approach is proposed by the theory that considers the education as socio-cultural phenomenon rather than activity carried out by a person that acquires knowledge from an organism taken out from the knowledge As noumen, the educational phenomenon is not conditioned space-time. Therefore, it is "void" of concrete, but it is "full" of totalising significance.